Visualizing myocardial injury from elective cardioversion with CMR. (8th February 2021) - Fischer, K; Riecker, C; Overney, S; Stucki, M; Tanner, H; Jung, B; Von Tengg-Kobligk, H; Eberle, B; Guensch, DP
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Association of Cardiothoracic Anaesthesiologists Research Grant Background: Despite everyday use of electrical interventions in cardiovascular care, the extent and type of concomitant myocardial injury is not fully understood. Current literature disagrees about the question whether and how cardioversion or defibrillation damage the myocardium, especially when serologic markers are used. Such markers are not always cardiac-specific, nor diagnostic for type and region of myocardial injury. These limitations may be overcome by parametric T1 and T2 mapping. We aimed to investigate whether the acute and long-term impact of electrical cardioversion on myocardial structure and function is detectable using CMR imaging. Methods: Patients scheduled for elective cardioversion were enrolled to undergo three CMR exams (3 Tesla): on the morning prior to cardioversion to assess pre-existing injury; two to five hours after cardioversion to assess the acute response; and six to ten weeks later to investigate chronic injury. The CMR exam studied left ventricular (LV) function, T2 mapping to measure edema, and extracellular volume (ECV) from T1 maps to measure diffuse fibrosis. Both the degree of injury and proportion (%) of myocardial area affected were analysed. Results: Eight patients completed the study, requiring 1-2 shocks (totalling 120-300 J biphasic energy) to achieve sinus rhythm. LV ejection fraction increased after cardioversion from 47 ± 13% to 55 ± 15% (p = 0.020), and was 52 ± 16% at the third exam (p = 0.199). Even prior to intervention, some patients showed edema (baseline T2 > 40ms) afflicting 49 ± 23% of their LV myocardium. Area affected by edema expanded to 72 ± 18% after cardioversion (p = 0.002) and returned to 54 ± 24% by the third exam. T2 rose from baseline (40.4 ± 1.8ms) after cardioversion acutely to 44.1 ± 5.2ms (p = 0.028) and normalized until the late exam (40.8 ± 3.1ms). Myocardial area affected by diffuse fibrosis (ECV > 30%) was 28.3 ± 9.4% at baseline and 38.8 ± 18.9% late after cardioversion (p = 0.018). Pathologic T2 increases (indicative of edema) were not observed in all patients, but individuals with higher baseline ECV also experienced greater T2 increase after cardioversion (r = 0.840, p = 0.036). Conclusion: Elective cardioversion improves LV systolic function, but also aggravates myocardial edema and possibly adds to diffuse fibrosis during several weeks thereafter. Such sequelae of cardioversion were observed mainly in patients with a greater burden of pre-existing myocardial injury. More data is needed to corroborate these preliminary findings and to study whether this type of myocardial injury predicts worse outcome. Moreover, changes in CMR markers caused by electrical interventions including defibrillation, may have the potential to confound diagnostic assessments of the underlying cardiac injury.